DESIGN, IMPLEMENTATION, AND EVALUATION OF AN ELECTRICAL ENERGY CONSUMPTION MONITORING SYSTEM IN HAJI RANI BUILDING USING ARDUINO UNO MICROCONTROLLER - Suhardi Rahman, Edi; Almunawati, Natasya; Tjandi, Yunus; Muis Mappalotteng , Abdul; Imran, Andi (Journal of Electrical Engineering and Informatics, 2025)
This study aims to design, implement, and evaluate a real-time electrical energy consumption monitoring system in the Haji Rani Building using the Arduino Uno microcontroller and the Blynk platform. The system integrates the PZEM-004T sensor for measuring voltage, current, power, and electrical energy, while the Wemos D1 Mini facilitates wireless data transmission via a Wi-Fi network. The research follows a Research and Development (R&D) methodology with a prototype development model. Data collection techniques include observation, documentation, and direct testing. The test results indicate that the developed system has a good level of accuracy, with an average deviation of 4.21% compared to standard measuring instruments. Despite minor deviations, the system successfully provides real-time monitoring with a fast response through the Blynk application, enabling remote access. Functionality evaluation using the Guttman scale, conducted by two content experts, confirms that the system meets the expected standards in terms of reliability, accuracy, and usability. However, the system's reliance on a stable Wi-Fi connection may affect monitoring reliability in areas with poor network coverage. Additionally, the accuracy of the PZEM-004T sensor, while acceptable for general monitoring, could be improved with more precise sensors. Future research should focus on integrating more accurate sensors, implementing machine learning algorithms for energy consumption analysis, and developing an automated IoT-based energy management system. By addressing these aspects, the proposed system can be further enhanced to improve energy efficiency and sustainability.